Culinary for The Spirits: The Reality of Cultural Acculturation of The Chinese Peranakan of Palembang - Sutami, Hermina; Kabul, Assa Rahmawati (Published by Confucius Institute UNS, 2024)
We usually talk about food, the way it is served, its types, and its beauty aspects in terms of satisfying the pleasures of the human eye and sense of taste. Therefore, in gastronomy, the things above receive great attention. Unsurprisingly, culinary art institutions have been established up to the academic level since decades ago. However, this paper presents a slightly different field of gastronomy, namely gastronomy for the ancestral spirits prayer ceremony, named coki/cuki prayer in Hokkian language (祖祭) which is still practiced today by the Chinese Peranakan of Palembang or we can say “Peranakan Palembang”, South Sumatra. This ritual ceremony, which is hundreds of years old is quite interesting, carried out by people of Chinese descent, both Totok and Peranakan, old and young generations. This paper focuses only on the Chinese Peranakan in Palembang. From here the question arises, why is this custom still maintained in modern times, even though the costs involved are not small? What type of food shows cultural acculturation? From a gastronomic point of view, how are the dishes served arranged? Are there rules? Research data consists of photos and information obtained from informants, and also researchers’ observations of Chinese Peranakan Palembang families because they are considered to know more about and carry out the rules related to the teaching of Confucianism (Tan, 1979). Shenism (Gondomono, 2013) and filial piety or 孝xiào in Confucian religious teachings are two philosophical thinking to know the reason why this ceremony is still carried out today. The research method is descriptive qualitative. The data from the informants will be sorted based on the type of dish, and how it is served, then will be described qualitatively, so that an understanding will be gained regarding the preservation of this prayer ceremony. The novelty of this paper is to increase knowledge about the existence of the culinary for spirits and the philosophical background.